SAT0520 Anti-il6-receptor tocilizumab in refractory uveitis associated to extraocular manifestations in patients with behÇet's disease. multicenter study of 11 patients. (12th June 2018) - Atienza-Mateo, B.; Martín-Varillas, J.L.; Calvo-Río, V.; Beltrán, E.; Martinez, L.; Valls, E.; Hernandez, M.; Atanes, A.; Cordero, M.; Nolla, J.M.; Carrasco, C.; Loricera, J.; et al.
Abstract : Objectives: To assess the efficacy of Tocilizumab (TCZ) in refractory uveitis associated to extraocular manifestations due to Behçet's disease (BD). Methods: Multicenter study of patients with BD refractory to standard systemic treatment (conventional immunosuppressive drugs and/or anti-TNF-α agents). Results: We studied 11 patients (7 men/4 women) (20 affected eyes); mean age 38.4±20.4 years. Uveitis was bilateral in 9 patients. The pattern of ocular involvement was: panuveitis (n=8; with retinal vasculitis in 4), anterior uveitis (n=2) and posterior uveitis (n=1). Cystoid macular oedema (CME) was present in 7 patients. The clinical course was recurrent (n=7) or chronic (n=4). Apart from the visual complications, at TCZ onset the following extraocular manifestations were present: oral and/or genital ulcers (n=7), arthritis (n=4), folliculitis/pseudofolliculitis (n=4), erythema nodosum (n=2), livedo reticularis (n=1), intestinal affection (n=1), and neurological involvement (n=2). Before TCZ, they had received systemic corticosteroids, conventional immunosuppressive drugs and biologic agents, adalimumab (n=8), infliximab (n=4), golimumab (n=3), canakinumab (n=1), or etanercept (n=1). TCZ was used in monotherapy or combined with conventional immunosuppressive drugs at 8 mg/kg/iv/4 weeks (n=10) or 162 mg/sc/week (n=1). TCZ yielded rapid and maintained improvement in all ocular parameters (TABLE ). After a mean follow-up of 9.5±8.05 months using TCZ, all patients experienced ocular improvement, with complete remission in 8 of them. However, TCZ was only effective in 3 of the patients with extraocular manifestations. This biologic agent had to be withdrawn in 2 cases, 1 due to a severe infusion reaction and 1 due to arthritis impairment. Abbreviations: CME, cystoid macular oedema; MRI, magnetic resonance imaging; TCZ, tocilizumab. Conclusions: TCZ appears to be useful in highly refractory BD-related uveitis. However, there are controversial results regarding its efficacy in the treatment of extraocular manifestations of BD. References: [1] Santos-Gómez M, Calvo-Río V, Blanco R, Beltrán E, Mesquida M, Adán A. The effect of biologic therapy different from infliximab or adalimumab in patients with refractory uveitis due to Behcet's disease: results of a multicenter open label study. Clin Exp Rheumatol2016;34(6Suppl 102):S34–S40. [2] Calvo-Río V, de la Hera D, Beltran-Catalan E, Blanco R, Hernandez M., Martinez-Costa L. Tocilizumab in uveitis refractory to other biologic drugs: a study of 3 cases and a literature review. Clin Exp Rheumatol2014;32(Suppl 84):S54–S57. [3] Calvo-Río V, Santos-Gomez M, Calvo I, et al. Anti-IL6-R Tocilizumab for Severe Juvenile Idiopathic Arthritis-Associated Uveitis Refractory to anti-TNF therapy. A multicenter study of 25 patients. Arthritis Rheumatol2016;69:668–75. Disclosure of Interest: None declared